Book Review: The International Law on Foreign Investment - Maulana, Mursal (Faculty of Law, Padjadjaran University, 2018)
Professor M. Sornarajah, prominent scholar in the field of investment law and C. J Koh Professor at Faculty of Law of the National University of Singapore presents his ambitious work on the contemporary issues on foreign investment in the context of public international law. Whatever criticism might land on Sornarajahâs ears in regard to this work, The International Law on Foreign Investment is undoubtedly an excellent work and one of the most remarkable publication.DOI:Â https://doi.org/10.22304/pjih.v5n2.a11